Figurative Language On Ahok Blasphemy In The Jakarta Post Newspaper: Critical Discourse Analysis - Km Tri Sutrisna Agustia (Denpasar Institute, 2022)
This study is investigated the use of figurative language in The Jakarta Post related to Ahok religion blasphemy during 2017 Jakarta gubernatorial elections. The research objectives were to explain the description and the interpretation dimension applied in the figurative language of Ahok blasphemy in The Jakarta Post newspaper. The study is analyzed under the Critical Discourse Analysis approach represented by Fairclough (1989). Qualitative method was applied in this research to get secondary data from the Jakarta Post Newspaper. On data collection, the researcher documented nine sentences of figurative language by using purposive sampling. In data analysis, the researcher used inductive technique to explain the data specifically then added with general explanation. The results showed that within vocabulary there were some word classes, classification schemes, meaning relation, euphemistic expression was applied along with formal-informal values, and positive-negative values; within grammatical features, action and attribution process, active-passive sentences, positive-negative sentences, clear and unclear agents were applied; within the textual structure, description, judgement/critique, an event, problem/solution, and compare/contrast structures were found. Within the interpretation dimension, the contents, the subjects, the relations, and the connections were clearly referred to the situational context